Application of N-dimethyl benzoylamidophosphate-based coordination compounds in the development of the technology for metallorganic light-emitting diodes (MOLED) - Kariaka, N. S.; Litsis, O. O.; Sliva, T. Yu.; Kolomzarov, Yu. V.; Minyailo, M. A.; Minakova, I. E.; Sorokin, V. M.; Amirkhanov, V. M. (Reports of the National Academy of Sciences of Ukraine, 2014)
Photoluminescent properties and thermal stability of the complexes EuL3 · 2H2O, EuL3Phen and TbL3 · 2H2O (HL = PhC(O)N(H)P(O)(OCH3)2, Phen = 1,10 -phenantroline) have been studied in order to find new promising electroluminescent materials. A method allowing the fabrication of films from non-aqueous solutions has been developed for the studied compounds. The obtained films were characterized by means of atomic force microscopy and fluorescence spectroscopy. Experimental samples of planar light-emitting heterostructures ITO/BDB/EuWi3 · 2H2O/Al and ITO/PEDOT:PSS/Complex/Al + Ca, ITO/PEDOT:PSS/PVK/Complex/Al + Ca (Complex = EuL3Phen or TbL3 · 2H2O) have been created, and their current-voltage characteristics are investigated.